Stock liquidity in forefront of anticipated announcements - Sergey Gelman; Roman Lushchikov (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
The paper studies the effects of anticipated earnings announcements on liquidity before the earnings announcement day, utilizing full limit order book data. We find very convincing supportive evidence of deteriorating liquidity due to the increase in information asymmetry, which is in line with existing literature. We contribute to the literature showing that supply and demand elasticities, and hence overall market depth, are much stronger adversely affected, as best bid and best ask quotes would suggest.
Keywords: G14; G12; G30; 330